Composite absorbent materials and sanitary products
Patent Information
- Application Number
- JP2020219818
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-29
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2040-12-29
AI Technical Summary
【0036】 本発明によれば、細孔容積に比して吸水量が低下することを抑制することができ、吸収性能に優れた複合吸収体、及びそれを有する衛生用品を提供することができる。
Smart Images

Figure 0007630276000002 
Figure 0007630276000003 
Figure 0007630276000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite absorbent body and a sanitary product having the same. [Background technology]
[0002] It is known that absorbent articles such as disposable diapers and sanitary napkins contain porous materials such as sponge materials as absorbents. For example, Patent Document 1 discloses an absorbent article containing a polymer foam material consisting of a hydrophilic flexible structure of interconnected open cells. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 3231320 Summary of the Invention [Problem to be solved by the invention]
[0004] According to the study by the inventors of the present application, porous materials such as the polymer foam material of Patent Document 1 have many pores with a relatively small pore radius. However, in a porous structure, moisture tends to be easily drawn into pores with a relatively large pore radius. Therefore, in a porous material having many pores with a small pore diameter as described above, moisture does not enter the pores with a small pore diameter during water absorption, and the amount of water absorption may be reduced compared to the pore volume.
[0005] The present invention has been made in consideration of such problems, and aims to provide a composite absorbent for sanitary products that can suppress a decrease in water absorption capacity relative to the pore volume and has excellent absorption performance, and a sanitary product having the same. [Means for solving the problem]
[0006] One aspect (Aspect 1) of the present invention is a composite absorbent for sanitary products for absorbing body fluids, comprising a polymer absorbent having a hydrophilic continuous skeleton and continuous pores, wherein in the polymer absorbent, the proportion of the pore volume of pores having a pore radius of 1 μm or more is 90% or more of the pore volume of all pores.
[0007] In the composite absorbent of this embodiment, the ratio of the pore volume of pores with a pore radius of 1 μm or more to the pore volume of all pores in the polymer absorbent is 90% or more. Therefore, when absorbing water, water is unlikely to enter pores with a relatively small pore radius, such as a pore radius of less than 1 μm, and even if water cannot enter, water can enter pores with a pore radius of 1 μm or more, ensuring a sufficient water absorption amount. Therefore, it is possible to suppress a decrease in the water absorption amount compared to the pore volume, and to obtain excellent absorption performance.
[0008] In another aspect (Aspect 2) of the present invention, in the composite absorbent of Aspect 1 above, the proportion of the pore volume of pores having a pore radius of 0.005 μm or less in the polymer absorbent is less than 10% of the pore volume of all pores.
[0009] In the composite absorbent of this embodiment, the proportion of the pore volume of pores with a very small pore radius, such as 0.005 μm or less, that have difficulty in absorbing water, is very small, and the proportion of the pore volume of pores with a large pore radius, such as 1 μm or more, that can absorb water, is large. This allows the pores of the polymer absorbent to be effectively used for water absorption, and ensures a sufficient amount of water absorption.
[0010] In still another aspect (Aspect 3) of the present invention, in the composite absorbent of Aspect 1 or 2 above, the polymer absorbent has a pore radius at the maximum pore volume of 500 μm or less.
[0011] In the composite absorbent of this embodiment, by setting the pore radius at the maximum pore volume to 500 μm or less, the continuous skeletal structure of the polymer absorbent can be prevented from being destroyed (crushed) during water absorption, making it easier to obtain an excellent absorption speed and ensuring a stable and sufficient water absorption amount (if the pore radius at the maximum pore volume is 500 μm or more, there is a risk that the continuous skeletal structure cannot be maintained during water absorption and may be crushed).
[0012] In yet another aspect (Aspect 4) of the present invention, in the composite absorbent described in any one of Aspects 1 to 3 above, the polymer absorbent is characterized in that the coefficient of variation of the pore distribution for pores having a pore radius of 1 μm or more is 1.4 or less.
[0013] The composite absorbent of this embodiment has a coefficient of variation of pore distribution of 1.4 or less, so that the variation of pore radius relative to the average value of pore radius is small, and the peak of the pore distribution is sharp near the average value of pore radius. Therefore, the polymer absorbent can absorb moisture almost uniformly from all directions and all surfaces. As a result, the pores of the polymer absorbent can be effectively used for water absorption, and a sufficient amount of water absorption can be secured.
[0014] In yet another aspect (Aspect 5) of the present invention, in the composite absorbent described in any one of Aspects 1 to 3 above, the polymer absorbent is characterized in that the coefficient of variation of the pore distribution in pores having a pore radius of 1 μm or more is greater than 1.4.
[0015] The composite absorbent of this embodiment has a coefficient of variation of pore distribution exceeding 1.4, so that the variation of pore radius with respect to the average value of pore radius is large, and the peak of the pore distribution is broad near the average value of pore radius. That is, the polymer absorbent has pores with small pore radius and pores with large pore radius. Therefore, in pores with small pore radius, capillary force is likely to work, and thus the water absorption speed is likely to be fast, and in pores with large pore radius, the water absorption volume is likely to be large. Therefore, due to the synergistic effect of the two, the polymer absorbent can instantly absorb a large amount of water inside the pores.
[0016] In yet another aspect (Aspect 6) of the present invention, in the composite absorbent described in Aspect 5 above, the polymer absorbent is characterized in that the portion of the polymer absorbent with a larger pore radius is broader than the portion with a smaller pore radius, relative to the pore radius corresponding to the maximum value of the pore volume in the curve showing the pore distribution.
[0017] In the composite absorbent of this embodiment, the polymer absorbent has the above-mentioned configuration, i.e., a configuration in which there are more pores with a large pore diameter than pores with a small pore radius. By having more pores with a large pore radius, the water absorption volume tends to be larger, and a larger amount of water can be absorbed inside the pores.
[0018] In yet another aspect (Aspect 7) of the present invention, in the composite absorbent described in Aspect 5 above, the polymer absorbent is characterized in that the portion on the side where the pore radius is smaller is broader than the portion on the side where the pore radius is larger, relative to the pore radius corresponding to the maximum value of the pore volume in the curve showing the pore distribution.
[0019] In the composite absorbent of this embodiment, the polymer absorbent has the above-mentioned structure, that is, a structure in which there are more pores with small pore diameters than pores with large pore radius. The presence of many pores with small pore radiuses facilitates capillary force, which makes it easier for the water absorption speed to increase, and allows water to be instantly absorbed inside the pores.
[0020] In yet another aspect (Aspect 8) of the present invention, in the composite absorbent described in any one of Aspects 1 to 3 above, the polymer absorbent is characterized in that there are at least two maximum values of pore volume in the curve showing the pore distribution.
[0021] In the composite absorbent of this embodiment, the polymer absorbent has the above-mentioned configuration, that is, pores having a predetermined small pore radius and a pore radius nearby it, and pores having a predetermined large pore radius and a pore radius nearby it are present. Therefore, in the pores with a relatively small pore radius, capillary force is likely to work, and therefore the water absorption speed is likely to be fast, and in the pores with a relatively large pore radius, the water absorption volume is likely to be large. Therefore, due to the synergistic effect of the two, the polymer absorbent can instantly absorb a large amount of water inside the pores.
[0022] In yet another aspect (Aspect 9) of the present invention, in the composite absorbent described in Aspect 8 above, the polymer absorbent is characterized in that the two maximum values of pore volume in the curve showing the pore distribution are such that the maximum value of the relatively small pore radius is larger than the maximum value of the relatively large pore radius.
[0023] In the composite absorbent of this embodiment, the polymer absorbent has the above-mentioned structure, that is, there are more pores with small pore diameters than pores with large pore radius. The presence of many pores with small pore radiuses facilitates capillary force, which makes it easier for the water absorption speed to increase, and allows water to be instantly absorbed inside the pores.
[0024] In yet another aspect (Aspect 10) of the present invention, in the composite absorbent described in Aspect 8 above, the polymer absorbent is characterized in that the two maximum values of pore volume in the curve showing the pore distribution are such that the maximum value of the relatively small pore radius is smaller than the maximum value of the relatively large pore radius.
[0025] In the composite absorbent of this embodiment, the polymer absorbent has the above-mentioned configuration, that is, there are more pores with a large pore diameter than those with a small pore radius. By having more pores with a large pore radius, the water absorption volume tends to be larger, and a larger amount of water can be absorbed inside the pores.
[0026] In still another aspect (Aspect 11) of the present invention, in the composite absorbent according to any one of Aspects 1 to 10 above, the polymer absorbent has a total pore volume of 0.9 mL / g or more.
[0027] In the composite absorbent of this embodiment, the total pore volume of the polymer absorbent is 0.9 mL / g or more, so that the polymer absorbent can have a sufficient pore volume, and therefore a sufficient water absorption amount can be ensured. In addition, the spaces (pores) for taking in the liquid to be absorbed (body fluid) in the porous body can be made less likely to collapse during absorption, and the water absorption amount and water absorption speed can be made less likely to decrease.
[0028] In still another aspect (aspect 12) of the present invention, in the composite absorbent according to any one of aspects 1 to 11 above, the polymer absorbent has a bulk density of 0.07 to 0.6 g / cm 3 It is characterized in that:
[0029] In the composite absorbent of this embodiment, the polymer absorbent has a bulk density of 0.07 to 0.6 g / cm 3 Therefore, the water absorption rate (DW) performance can be made 6mL / 30sec or more. In other words, since the water absorption rate is increased, the polymer absorbent can instantly absorb water inside the pores.
[0030] In still another aspect (aspect 13) of the present invention, in the composite absorbent according to any one of aspects 1 to 12 above, the polymer absorbent is a monolithic absorbent.
[0031] The composite absorbent of this embodiment can quickly absorb moisture because the polymer absorbent is a monolithic absorbent.
[0032] In yet another aspect (Aspect 14) of the present invention, in the composite absorbent described in any one of Aspects 1 to 13 above, the polymer absorbent is a hydrolysate of a crosslinked polymer of a (meth)acrylic acid ester and a compound containing two or more vinyl groups in one molecule, and is characterized in that it contains at least one -COONa group.
[0033] In the composite absorbent of this embodiment, since the polymer absorbent has the above-mentioned specific configuration, when absorbing body fluids, the hydrophilic continuous skeleton is easily extended and the continuous pores are easily expanded, so that a larger amount of body fluid can be taken up into the continuous pores more quickly, and the absorbent can exhibit even better absorption performance.
[0034] A further aspect (aspect 15) of the present invention is a sanitary product comprising the composite absorbent body according to any one of aspects 1 to 14 above.
[0035] The sanitary product of this embodiment has the composite absorbent body of any one of the above-mentioned embodiments 1 to 14, and therefore can exhibit excellent absorption performance as a sanitary product. Effect of the Invention
[0036] According to the present invention, it is possible to provide a composite absorbent body having excellent absorption performance, which can suppress a decrease in water absorption amount relative to the pore volume, and a sanitary product having the same. [Brief description of the drawings]
[0037] [Figure 1] FIG. 1 is a schematic plan view of a light incontinence pad 1 in an expanded state, as viewed in the thickness direction from the skin-facing surface side. [Diagram 2] FIG. 2 is a diagram illustrating a manufacturing process of absorbent A, which is an example of a polymer absorbent. [Diagram 3] FIG. 3 is an SEM photograph of absorbent A at a magnification of 50 times. [Figure 4] FIG. 4 is a SEM photograph of absorbent A at a magnification of 100 times. [Diagram 5] FIG. 5 is an SEM photograph of absorbent A at a magnification of 500 times. [Figure 6] FIG. 6 is a SEM photograph of absorbent A at a magnification of 1000 times. [Figure 7] FIG. 7 is a SEM photograph of absorbent A at a magnification of 1500 times. [Figure 8]FIG. 8 is a graph showing the relationship between the pore radius of the pores of absorbent A and the cumulative pore volume. [Figure 9] FIG. 9 is a graph showing the relationship between the pore radius of the pores of absorbent A and the differential pore volume. [Figure 10] FIG. 10 is a graph showing the relationship between the bulk density and the absorption performance (DW) in absorbent A. [Figure 11] FIG. 11 is a schematic diagram showing a measurement device used in the pressureless DW method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0038] A preferred embodiment of the composite absorbent body of the present invention will be described in detail below using a light incontinence pad 1, which is an example of a sanitary product to which the composite absorbent body can be applied. In this specification, unless otherwise specified, the term "planar view" simply refers to "viewing an object (e.g., a light incontinence pad, a composite absorbent, etc.) placed in an unfolded state on a horizontal surface from above in the vertical direction (from the top sheet side if the object is a sanitary product) in the thickness direction of the object."
[0039] In this specification, the "longitudinal direction" refers to the "longer direction of a vertically elongated object (e.g., a light incontinence pad, a composite absorbent, etc. in an unfolded state) when viewed in a plane", the "width direction" refers to the "shorter direction of a vertically elongated object when viewed in a plane", and the "thickness direction" refers to the "perpendicular direction to an object placed on a horizontal surface in an unfolded state", and these longitudinal, width and thickness directions are perpendicular to each other.
[0040] Furthermore, in this specification, unless otherwise specified, in the thickness direction of the light incontinence pad 1, the "proximal side relative to the wearer's skin when the light incontinence pad 1 is worn" is referred to as the "skin-facing side", and the "distal side relative to the wearer's skin when the light incontinence pad 1 is worn" is referred to as the "non-skin-facing side".
[0041] [Light incontinence pads] FIG. 1 is a schematic plan view of a light incontinence pad 1 in an expanded state to which a composite absorbent body 4 according to one embodiment of the present invention is applied. 1, the light incontinence pad 1 has a longitudinal direction L and a width direction W in plan view, and has a vertically elongated outer shape with two longitudinal end edges protruding outward in an arc shape in the longitudinal direction. Note that the outer shape of the light incontinence pad 1 is not limited to this, and any shape (e.g., oval, rectangular, hourglass, etc.) can be adopted as long as it is vertically elongated according to various applications and usage modes.
[0042] The light incontinence pad 1 basically comprises, in the thickness direction, a liquid-permeable top sheet 2 which forms the surface of the light incontinence pad 1 facing the skin, a back sheet 3 which forms the surface of the light incontinence pad 1 not facing the skin, and a composite absorbent 4 located between these sheets. The light incontinence pad 1 further includes an adhesive portion (not shown) that is disposed on the surface of the backsheet 3 that does not face the skin and that adhesively fixes the light incontinence pad 1 to the inner surface of the wearer's clothing, such as underwear.
[0043] It should be noted that the light incontinence pad 1 is not limited to this configuration, and may, for example, comprise a pair of side sheets for forming a leak-proof wall, which are positioned at both ends of the light incontinence pad 1 in the width direction W at a position closer to the skin-facing side than the top sheet 2 and extend in the longitudinal direction L, and a plurality of elastic members arranged along the longitudinal direction L on each of the pair of side sheets.
[0044] In the light incontinence pad 1, the composite absorbent 4 is located between the top sheet 2 and the back sheet 3, and is formed from an absorbent material that can absorb bodily fluids such as urine and menstrual blood that are discharged from the wearer and pass through the top sheet 2. The composite absorbent 4 contains a polymer absorbent having a hydrophilic continuous skeleton and continuous pores, and in this embodiment, further contains a super absorbent polymer (SAP). Furthermore, this polymer absorbent exhibits a unique water absorption behavior in which, when absorbing water, the water is incorporated into the above-mentioned continuous framework and then into the continuous pores.
[0045] In the composite absorbent 4, when the polymer absorbent having the above-mentioned hydrophilic continuous skeleton and continuous pores absorbs body fluids such as urine or menstrual blood, the hydrophilic continuous skeleton instantly takes in the body fluid due to osmotic pressure and expands, expanding the volume of the continuous pores, and the body fluid can be further taken in by the expanded continuous pores, so that the composite absorbent 4 can instantly absorb a large amount of body fluid. In this embodiment, the absorbed body fluid can be further transferred to the SAP with high water retention capacity and steadily retained in the SAP. This allows the composite absorbent body 4 to exhibit high absorption performance as an absorbent body.
[0046] Therefore, the light incontinence pad 1 including such a composite absorbent body 4 can also exhibit excellent absorption performance as a light incontinence pad.
[0047] Various constituent members of sanitary goods to which the composite absorbent body of the present invention is applied will be described in more detail below using the above-mentioned light incontinence pad 1.
[0048] (Surface sheet) 1, in the above-mentioned light incontinence pad 1, the top sheet 2 has a vertically elongated outer shape in a plan view, extending from one edge to the other edge in the longitudinal direction L of the light incontinence pad 1 and also extending from the vicinity of one edge to the vicinity of the other edge in the width direction W of the light incontinence pad 1. The top sheet 2 is arranged at a position on the skin-facing side in the thickness direction of the light incontinence pad 1 and is composed of a liquid-permeable sheet-like member that forms a contact surface that can come into contact with the wearer's skin, i.e., the surface of the light incontinence pad 1 facing the skin.
[0049] As shown in FIG. 1, the top sheet 2 is slightly larger in the longitudinal direction L and width direction W than the composite absorbent 4 arranged on the non-skin-facing side of the top sheet 2, and is joined at its peripheral portion to the back sheet 3 located on the non-skin-facing side.
[0050] In the present invention, the outer shape, various dimensions, basis weight, etc. of the top sheet are not particularly limited as long as they can be used as a top sheet for sanitary products, and any outer shape, various dimensions, basis weight, etc. can be adopted depending on the desired liquid permeability, feel to the skin, flexibility, strength, etc.
[0051] (Back sheet) In the above-mentioned light incontinence pad 1, the back sheet 3 has a vertically elongated outer shape in a plan view, extending from one side edge to the other side edge in the longitudinal direction L of the light incontinence pad 1 and also from one side edge to the other side edge in the width direction W of the light incontinence pad 1. The back sheet 3 is disposed at a position on the non-skin-facing side in the thickness direction of the light incontinence pad 1 to form the non-skin-facing surface of the light incontinence pad 1, and is composed of a liquid-impermeable sheet-like member that prevents body fluids such as urine and menstrual blood that have permeated the composite absorbent 4 from leaking out of the light incontinence pad 1.
[0052] In the present invention, the outer shape, various dimensions, basis weight, etc. of the back sheet are not particularly limited as long as they can be used as a back sheet of a sanitary product, and any outer shape, various dimensions, basis weight, etc. can be adopted according to the desired leak prevention performance, breathability, strength, etc.
[0053] (Composite absorber) In the above-mentioned light incontinence pad 1, as shown in Figure 1, when viewed in a plane, the composite absorbent 4 extends over a wide area in the longitudinal direction L from near one edge in the longitudinal direction L to near the other edge, centered on the center of the light incontinence pad 1 in the longitudinal direction L and width direction W, and also extends over a wide area in the width direction W from near one edge in the width direction W to near the other edge, and further has a vertically elongated outer shape in which the two longitudinal edges protrude in an arc shape toward the outward longitudinal direction.
[0054] More specifically, the composite absorbent body 4 has a constricted portion in the longitudinal center when viewed in a plane, the constricted portion having a widthwise length relatively smaller than other portions, and further has a minimum width portion in this constricted portion having the minimum width of the composite absorbent body 4, and a maximum width portion on the longitudinal outer side of the constricted portion having the maximum width of the composite absorbent body 4.
[0055] The composite absorbent 4 is disposed between the top sheet 2 and the back sheet 3 in the thickness direction of the light incontinence pad 1, and is formed from a predetermined absorbent member capable of absorbing and retaining bodily fluids such as urine and menstrual blood that have permeated the top sheet 2, and this absorbent member is composed of absorbent materials such as polymer absorbents, hydrophilic fibers, and highly absorbent polymers, which will be described later, and a sheet such as tissue that retains it. In other words, the composite absorbent means an absorbent member composed of an absorbent material capable of absorbing and retaining bodily fluids, and a sheet that retains it.
[0056] In the light incontinence pad 1, the composite absorbent body 4 is bonded to each of the top sheet 2 and the back sheet 3 by any adhesive such as a hot melt adhesive.
[0057] The composite absorbent 4 contains a polymer absorbent having a hydrophilic continuous skeleton and continuous pores and exhibiting the above-mentioned unique water absorption behavior, as described above, and further contains a superabsorbent polymer in this embodiment. The polymer absorbent will be described later, and the superabsorbent polymer is a powder or granular material made of a highly absorbent polymer such as a sodium acrylate copolymer known in the art, and is called SAP (Super Absorbent Polymer).
[0058] The composite absorbent 4 may contain only the above-mentioned polymer absorbent as the water-absorbing material, or may contain only the polymer absorbent and the superabsorbent polymer, or may further contain a water-absorbing material known in the art in addition to these. Examples of such water-absorbing materials include hydrophilic fibers, and more specifically, pulp fibers (e.g., ground pulp, etc.), and cellulosic fibers such as cotton, rayon, and acetate.
[0059] The composite absorbent body 4 may have a configuration in which any water-absorbent material such as such a polymer absorbent and a superabsorbent polymer is covered with a wrap sheet such as a hydrophilic tissue.
[0060] In the present invention, the outer shape, various dimensions, basis weight, etc. of the composite absorbent body are not particularly limited as long as they do not impair the effects of the present invention, and any outer shape, various dimensions, basis weight, etc. can be adopted according to the desired water absorbency, flexibility, strength, etc.
[0061] The polymer absorbent used in the composite absorbent of the present invention will be described in more detail below.
[0062] [Polymer absorbent] In the present invention, the polymer absorbent is not particularly limited as long as it has a hydrophilic continuous skeleton and continuous pores, and exhibits a unique water absorption behavior in which, when absorbing moisture, the moisture is taken into the above-mentioned continuous skeleton and then into the continuous pores. Such a polymer absorbent is, for example, a hydrolyzate of a crosslinked polymer of two or more monomers including at least a (meth)acrylic acid ester, and a polymer compound having at least one hydrophilic group in the functional group. More specifically, a polymer compound is a hydrolyzate of a crosslinked polymer of a (meth)acrylic acid ester and a compound containing two or more vinyl groups in one molecule, and has at least a -COONa group. Such a polymer absorbent is an organic porous body having at least one or more -COONa groups in one molecule, and may further have a -COOH group. The -COONa groups are distributed approximately uniformly in the skeleton of the porous body.
[0063] When the polymer absorbent is a hydrolysate of a crosslinked polymer of such a (meth)acrylic acid ester and a compound containing two or more vinyl groups in one molecule and contains at least one -COONa group, as described below, the hydrophilic continuous skeleton becomes easier to extend (i.e., expand) when absorbing body fluids such as urine and menstrual blood, and the continuous pores also become easier to expand, so that a larger amount of body fluid can be taken in the continuous pores more quickly, and the absorbent can exhibit even better absorption performance.
[0064] In this specification, the (meth)acrylic acid ester refers to an acrylic acid ester or a methacrylic acid ester.
[0065] In such a polymer absorbent formed by a hydrolysis product of a cross-linked polymer of a (meth)acrylic acid ester and divinylbenzene, a hydrophilic continuous skeleton is formed by an organic polymer having at least -COONa groups, and the skeleton has communicating holes (interconnected pores) that serve as absorption sites for the liquid to be absorbed (i.e., body fluids such as urine and menstrual blood). In addition, since the hydrolysis treatment converts the -COOR groups (that is, carboxylate groups) of the crosslinked polymer into -COONa groups or -COOH groups (see FIG. 2), the polymer absorbent may have -COOR groups.
[0066] The presence of -COOH and -COONa groups in the organic polymer forming the hydrophilic continuous backbone can be confirmed by analysis using infrared spectroscopy and a quantitative method for weakly acidic ion exchange groups.
[0067] Here, Fig. 2 is a diagram for explaining the manufacturing process of absorbent A, which is an example of a polymer absorbent. In this Fig. 2, the upper diagram shows the constituent raw materials for polymerization, the middle diagram shows monolith A, which is a crosslinked polymer of (meth)acrylic acid ester and divinylbenzene, and the lower diagram shows absorbent A obtained by subjecting monolith A in the middle diagram to hydrolysis and drying treatment.
[0068] Hereinafter, an explanation will be given using absorbent A, which is an example of a polymer absorbent and is formed from a hydrolysate of a crosslinked polymer of a (meth)acrylic acid ester and divinylbenzene.
[0069] The polymer absorbent is not limited to the absorbent A, but may be a hydrolysate of a cross-linked polymer of a (meth)acrylic acid ester and a compound having two or more vinyl groups in one molecule, or a hydrolysate of a cross-linked polymer of two or more monomers including at least a (meth)acrylic acid ester. However, when the polymer absorbent is a monolithic absorbent, it has the advantage that it can quickly absorb body fluids and that the body fluid temporarily held in the polymer absorbent can be more steadily transferred to the SAP.
[0070] In the following description, "Monolith A" refers to an organic porous material consisting of a crosslinked polymer of (meth)acrylic acid ester and divinylbenzene before hydrolysis treatment, and may be referred to as a "monolithic organic porous material." In addition, "absorbent A" is a hydrolyzate of a crosslinked polymer (monolith A) of (meth)acrylic acid ester and divinylbenzene after hydrolysis and drying. In the following description, absorbent A refers to the absorbent in a dry state.
[0071] First, the structure of absorbent A will be described. As described above, absorbent A has a hydrophilic continuous skeleton and continuous pores. As shown in Figure 2, absorbent A, which is an organic polymer having a hydrophilic continuous skeleton, is obtained by cross-linking polymerizing (meth)acrylic acid ester, which is a polymerization monomer, and divinylbenzene, which is a cross-linking monomer, and further hydrolyzing the obtained cross-linked polymer (monolith A).
[0072] The organic polymer that forms a hydrophilic continuous skeleton has, as structural units, a polymerized residue of an ethylene group (hereinafter referred to as "structural unit X") and a cross-linked polymerized residue of divinylbenzene (hereinafter referred to as "structural unit Y"). Furthermore, the polymerized residue of the ethylene group (structural unit X) in the organic polymer forming the hydrophilic continuous skeleton has a -COONa group generated by hydrolysis of the carboxylate group, or both a -COOH group and a -COONa group. When the polymerized monomer is a (meth)acrylic acid ester, the polymerized residue of the ethylene group (structural unit X) has a -COONa group, a -COOH group, and an ester group.
[0073] In the absorbent A, the ratio of the crosslinked polymer residue of divinylbenzene (structural unit Y) in the organic polymer forming the hydrophilic continuous skeleton is, for example, 0.1 to 30 mol %, preferably 0.1 to 20 mol %, based on the total structural units. For example, in the absorbent A in which butyl methacrylate is used as the polymerization monomer and divinylbenzene is used as the crosslinked monomer, the ratio of the crosslinked polymer residue of divinylbenzene (structural unit Y) in the organic polymer forming the hydrophilic continuous skeleton is, for example, about 3 mol %, preferably 0.1 to 10 mol %, more preferably 0.3 to 8 mol %, based on the total structural units. Furthermore, when the ratio of cross-linked polymerized residues of divinylbenzene in the organic polymer forming the hydrophilic continuous skeleton is 0.1 mol % or more, the strength of absorbent A is less likely to decrease, and when the ratio of cross-linked polymerized residues of divinylbenzene is 30 mol % or less, the absorption amount of the liquid to be absorbed is less likely to decrease.
[0074] In addition, in the absorbent A, the organic polymer forming the hydrophilic continuous skeleton may be composed only of the structural unit X and the structural unit Y, or may have, in addition to the structural unit X and the structural unit Y, a structural unit other than the structural unit X and the structural unit Y, that is, a polymerized residue of a monomer other than a (meth)acrylic acid ester and divinylbenzene.
[0075] Examples of structural units other than the structural unit X and the structural unit Y include polymerized residues of monomers such as styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, glycidyl (meth)acrylate, isobutene, butadiene, isoprene, chloroprene, vinyl chloride, vinyl bromide, vinylidene chloride, tetrafluoroethylene, (meth)acrylonitrile, vinyl acetate, ethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and trimethylolpropane tri(meth)acrylate.
[0076] The proportion of structural units other than the structural unit X and the structural unit Y in the organic polymer that forms the hydrophilic continuous skeleton is, for example, 0 to 50 mol %, and preferably 0 to 30 mol %, relative to all structural units.
[0077] In addition, the absorbent A preferably has a hydrophilic continuous skeleton having a thickness of 0.1 to 100 μm. When the thickness of the hydrophilic continuous skeleton of the absorbent A is 0.1 μm or more, the spaces (pores) for taking in the liquid to be absorbed (body fluid) in the porous body are less likely to collapse during absorption, and the absorption amount is less likely to decrease. On the other hand, when the thickness of the hydrophilic continuous skeleton is 100 μm or less, an excellent absorption speed is easily obtained. However, the thickness of the continuous skeleton can be obtained, for example, from an SEM observation photograph of the absorbent A.
[0078] In addition, since the pore structure of the hydrophilic continuous skeleton of absorbent A is an open-cell structure, the thickness of the continuous skeleton is measured by evaluating the cross section of the skeleton that appears on the test piece for electron microscope measurement. The continuous skeleton is often polygonal in shape because it is formed by the gaps between water (water droplets) removed by the dehydration and drying process after hydrolysis. Therefore, the thickness of the continuous skeleton is the average value of the diameter (μm) of the circle circumscribing the polygonal cross section. In rare cases, there may be small holes in the polygon, in which case the circumscribing circle of the polygonal cross section surrounding the small holes is measured.
[0079] Furthermore, the absorbent A preferably has an average diameter of interconnected pores of 1 to 1000 μm. When the average diameter of interconnected pores in the absorbent A is 1 μm or more, the spaces (pores) for taking in the liquid to be absorbed (body fluid) in the porous body are less likely to collapse during absorption, and the absorption rate is less likely to decrease. On the other hand, when the average diameter of interconnected pores is 1000 μm or less, an excellent absorption rate is easily obtained.
[0080] The average diameter (μm) of the interconnected pores of absorbent A can be measured by mercury intrusion porosimetry, and the maximum value of the pore distribution curve obtained by the mercury intrusion porosimetry is used. Regardless of the ionic form of absorbent A, samples for measuring the average diameter of interconnected pores are those dried for 18 hours or more in a reduced pressure dryer set at a temperature of 50°C. The final pressure reached is 0 Torr.
[0081] Here, FIG. 3 is an SEM photograph of absorbent A at a magnification of 50 times, FIG. 4 is an SEM photograph of absorbent A at a magnification of 100 times, FIG. 5 is an SEM photograph of absorbent A at a magnification of 500 times, FIG. 6 is an SEM photograph of absorbent A at a magnification of 1000 times, and further, FIG. 7 is an SEM photograph of absorbent A at a magnification of 1500 times. The absorbents A shown in these Figs. 3 to 7 are examples of absorbents that use butyl methacrylate as a polymerization monomer and divinylbenzene as a cross-linking monomer, and each has a cubic structure with a side length of 2 mm.
[0082] 3 to 7 has a large number of cellular macropores and further has portions where these cellular macropores overlap. Absorbent A has an open cell structure in which the overlapping portions of the macropores form common openings (mesopores), i.e., it has an open cell structure (open macropore structure).
[0083] The overlapping portions of the macropores form common openings (mesopores) having an average diameter in a dry state of 1 to 1000 μm, preferably 10 to 200 μm, and particularly preferably 20 to 100 μm, and most of them have an open pore structure. When the average diameter of the mesopores in a dry state is 1 μm or more, the absorption rate of the liquid to be absorbed is improved. On the other hand, when the average diameter of the mesopores in a dry state is 1000 μm or less, the absorbent A is less likely to become embrittled. The number of overlapping macropores in each macropore is about 1 to 12, and in most cases, about 3 to 10.
[0084] In addition, since absorbent A has such an open cell structure, macropores and mesopores can be uniformly formed, and there is an advantage in that the pore volume and specific surface area can be significantly increased compared to the particle agglomeration type porous bodies as described in JP-A-8-252579 and the like.
[0085] The continuous pores of the absorbent A are a plurality of pores (voids) that are connected to each other. The total pore volume of the pores (voids) of the absorbent A is preferably 0.5 to 50 mL / g, more preferably 0.9 to 40 mL / g, and even more preferably 2 to 30 mL / g. When the total pore volume of the absorbent A is 0.5 mL / g or more, a sufficient pore volume can be secured in the absorbent A, and therefore a sufficient amount of water absorption can be secured. In addition, the space (pores) for taking in the liquid to be absorbed (body fluid) of the porous body can be made difficult to collapse during absorption, and the amount and speed of water absorption can be made difficult to decrease. On the other hand, when the total pore volume of the absorbent A is 50 mL / g or less, the strength of the absorbent A can be made difficult to decrease.
[0086] The total pore volume can be measured by mercury intrusion porosimetry. The sample for measuring the total pore volume is dried for 18 hours or more in a vacuum dryer set at a temperature of 50°C, regardless of the ion form of absorbent A. The final pressure is 0 Torr. The mercury intrusion porosimetry can obtain the cumulative (integrated) pore volume distribution (relationship between pore radius and cumulative pore volume) and the log differential pore volume distribution (relationship between pore radius and log differential pore volume), and can calculate the total pore volume (mL / g), average pore radius (μm), maximum pore radius (μm), pore volume (mL / g) and ratio (%) of pores with a given pore radius or more (or less), and the coefficient of variation of the pore volume. The maximum pore diameter (μm) refers to the pore radius of the pore that shows the maximum pore volume. In addition, the pore volume (mL / g) for each pore radius is the log differential pore volume (mL / g) in the log differential pore volume distribution.
[0087] Here, in the pores (voids) of the absorbent A, the ratio of the pore volume of pores with a pore radius of 1 μm or more to the pore volume of all pores (total pore volume) is 90% or more, preferably 93% or more, and more preferably 95% or more. When the ratio of the pore volume of pores with a pore radius of 1 μm or more is 90% or more, during water absorption, water is less likely to enter pores with a relatively small pore radius, such as a pore radius of less than 1 μm, and even if water does not enter, a sufficient amount of water absorption can be ensured. This makes it possible to suppress a decrease in the amount of water absorption compared to the pore volume, and excellent absorption performance can be obtained.
[0088] In the pores of the absorbent A, the proportion of the pore volume of pores with a pore radius of 0.005 μm or less is preferably less than 10% of the pore volume of all pores (total pore volume), and the proportion of the pore volume of pores with a pore radius of 0.05 μm or less is more preferably less than 10% of the pore volume of all pores (total pore volume). In the absorbent A, the proportion of the pore volume of pores with a pore radius of 0.005 μm or less that are very small and difficult to absorb water is very small, and the proportion of the pore volume of pores with a pore radius of 1 μm or more that are large and capable of absorbing water is large (90% or more). This allows the pores of the absorbent A to be effectively used for water absorption, and a sufficient amount of water absorption can be ensured.
[0089] In addition, the pores of the absorbent A preferably have a pore radius of (0.5 μm or more) 500 μm or less at the pores showing the maximum pore volume, more preferably 300 μm or less, and more preferably 150 μm or less. By making the pore radius at the maximum pore volume 500 μm or less, it is possible to suppress the continuous skeleton structure of the absorbent A from being broken (crushed) during water absorption, making it easy to obtain an excellent absorption speed, and ensuring a stable and sufficient amount of water absorption. If the pore radius at the maximum pore volume is 500 μm or more, there is a risk that the continuous skeleton structure cannot be maintained during water absorption and may be crushed.
[0090] Furthermore, the pores of absorbent A may have a coefficient of variation of pore distribution (pore volume) of 1.4 or less for pores with a pore radius of 1 μm or more. When the coefficient of variation of the pore distribution is 1.4 or less, the variation of the pore radius relative to the average value of the pore radius is small, and the peak of the pore distribution is sharp near the average value of the pore radius. Therefore, absorbent A can absorb moisture almost uniformly from all directions and all surfaces. This allows the pores of the polymer absorbent to be effectively used for water absorption, ensuring a sufficient amount of water absorption.
[0091] On the other hand, the pores of the absorbent A may have a coefficient of variation of the pore distribution (pore volume) in the pores with a pore radius of 1 μm or more. In this case, since the coefficient of variation of the pore distribution is more than 1.4, the variation of the pore radius with respect to the average value of the pore radius is large, and the peak of the pore distribution is broad near the average value of the pore radius. That is, the absorbent A has pores with small pore radius and pores with large pore radius. Therefore, the capillary force is likely to work in the pores with a small pore radius, and therefore the water absorption speed is likely to be fast, and the water absorption volume is likely to be large in the pores with a large pore radius. Therefore, due to the synergistic effect of the two, the absorbent A can instantly absorb a large amount of water inside the pores.
[0092] Here, in the case of the pores of the absorbent A, when the peak of the pore distribution is broad, the portion on the side of the pore radius larger than the portion on the side of the pore radius smaller than the pore radius corresponding to the maximum value of the pore volume in the curve showing the pore distribution may be broader. In this case, the absorbent A has a configuration in which there are more pores with a larger pore diameter than pores with a smaller pore radius. Therefore, by having more pores with a larger pore radius, the water absorption volume tends to be larger, and a larger amount of water can be absorbed inside the pores.
[0093] On the other hand, even if the pores of absorbent A have a broad peak in the pore distribution, the portion with a smaller pore radius may be broader than the portion with a larger pore radius with respect to the pore radius corresponding to the maximum value of the pore volume in the curve showing the pore distribution. In this case, absorbent A has a configuration in which there are more pores with a smaller pore radius than pores with a larger pore radius. The presence of more pores with a smaller pore radius makes it easier for capillary force to work, which makes it easier for the water absorption speed to be faster, and allows moisture to be instantly absorbed inside the pores.
[0094] Furthermore, in the pores of the absorbent A, there may be at least two maximum values of the pore volume in the curve showing the pore distribution. In this case, in the absorbent A, there are pores having a predetermined small pore radius and a pore radius nearby it, and pores having a predetermined large pore radius and a pore radius nearby it. Therefore, in the pores with a relatively small pore radius, capillary force is likely to work, and therefore the water absorption speed is likely to be fast, and in the pores with a relatively large pore radius, the water absorption volume is likely to be large. Therefore, due to the synergistic effect of the two, the polymer absorbent can instantly absorb a large amount of water inside the pores.
[0095] Here, in the case where there are two maxima of the pore volume in the pores of the absorbent A, the maximum value of the pore volume in the curve showing the pore distribution may be larger for the relatively small pore radius than for the relatively large pore radius. In this case, there are more pores with small pore diameters than pores with large pore radius in the absorbent A. The presence of more pores with small pore radiuses makes it easier for capillary force to work, which makes it easier for the water absorption speed to be faster, and allows water to be instantly absorbed inside the pores.
[0096] On the other hand, even if there are two maxima in the pore volume of the pores of absorbent A, the two maxima in the pore volume in the curve showing the pore distribution may be such that the maximum value of the relatively small pore radius is smaller than the maximum value of the relatively large pore radius. In this case, absorbent A has more pores with large pore diameters than pores with small pore radius. The presence of more pores with large pore radiuses makes it easier for the water absorption volume to become larger, and a larger amount of water can be absorbed inside the pores.
[0097] In addition, the pores of absorbent A have a bulk density of 0.07 to 0.6 g / cm 3 and preferably 0.1 to 0.4 g / cm 3 More preferably, the density is 0.15 to 0.35 g / cm 3 In that case, as described later, the water absorption rate (DW) performance can be 6 mL / 30 sec. or more, more preferably 10 mL / 30 sec. or more, and even more preferably 12 mL / 30 sec. or more. That is, since the water absorption rate is increased, the polymer absorbent can instantly absorb water inside the pores.
[0098] <How to measure water absorption rate (DW)> The water absorption rate of the absorbent is measured by the non-pressurized DW (Demand Wettability) method. FIG. 11 is a schematic diagram showing a measuring device used in the non-pressurized DW method. A DW device (Demand Wettability device, manufactured by Taiyo Create Co., Ltd.) 11 is used as such a measuring device. As shown in the figure, the DW device 11 includes a burette 12 (50 ml graduated capacity, 86 cm long, 1.05 cm inner diameter), a rubber stopper 13, an air inlet capillary (3 mm inner diameter at tip) 14, a cock 15, a cock 16, a measuring table 17, a liquid outlet (3 mm inner diameter) 18, a cylinder 19, and a test liquid 20. A conduit (7 mm inner diameter) is attached from the burette 12 to the measuring table 17. A 0.9% sodium chloride aqueous solution is used as the test liquid. The measurement is performed in an atmosphere of 25°C x 50% humidity RH (constant temperature and humidity room).
[0099] The measurement procedure is as follows. (1) With both cocks 15, 16 of the DW apparatus 11 closed, pour the test liquid 20 above the 0 point (the top of the burette 12 scale (0 ml line)) and place the rubber stopper 13 on the top of the burette 12 to seal it. (2) After placing filter paper on the liquid outlet 18 of the measuring table 17, open both cocks 15 and 16 and adjust the liquid level to the zero point while using the filter paper to suck up the liquid coming out of the liquid outlet 18. After adjustment, close the cocks 15 and 16. (3) Place 100% wood pulp tissue (basis weight 15±1 gsm, thickness 0.1±0.02 mm when measured with a nonwoven fabric thickness meter at a pressure of 3 g / cm2) on the measurement table 17 with the liquid outlet 18 at the center. (4) A cylinder 19 with a diameter of 30 mm is placed in the center of the tissue, and a test object (polymeric absorbent) is placed in it, centered on the liquid outlet 18. The test object is placed in the cylinder 19, and its periphery is constrained by the cylinder 19. (5) Open the taps 15 and 16, and the measurement start time is the time when the test object begins to absorb the test liquid 20 and the first bubble introduced from the air inlet capillary 14 reaches the surface of the test liquid 20 in the burette 12 (the time when the surface of the test liquid 20 in the burette 12 drops). (6) Continuously read the amount of test liquid 20 in the burette 12 (the amount of test liquid 20 absorbed by the test object) M (ml). (7) The amount of absorption of the test object after a predetermined time has elapsed since the start of absorption (in this embodiment, after 30 seconds has elapsed) is calculated using the DW method: Absorption amount (ml / g) = M (ml) / (weight (g) of the test object (polymer absorbent)).
[0100] Hereinafter, the state when the absorbent A comes into contact with a liquid such as a body fluid (hereinafter simply referred to as "body fluid") will be described, but the same applies to the state when the composite absorbent 4 containing the absorbent A comes into contact with a body fluid. Furthermore, since the mass of absorbed body fluid is approximately proportional to the amount of body fluid, in the following description, the mass of body fluid may be simply referred to as the "amount of body fluid".
[0101] First, the continuous pores of the absorbent A shown in Figs. 3 to 7 are pores in which a plurality of pores (voids) are interconnected, and it is possible to visually confirm with the naked eye that a large number of voids are provided from the outside. When body fluids such as urine or menstrual blood come into contact with the absorbent A having such a large number of pores, the hydrophilic continuous skeleton first instantly absorbs a portion of the body fluid due to osmotic pressure and expands (i.e., expands). This expansion of the continuous skeleton occurs in almost all directions. The absorbent A thus absorbs a certain amount of body fluid and becomes enlarged, and is then able to absorb a further predetermined amount of body fluid into the expanded continuous pores due to capillary action. In this way, the absorbent A exhibits a unique water absorption behavior in which, when absorbing water (body fluid), the water is absorbed into the hydrophilic continuous skeleton and then absorbed by the continuous pores.
[0102] Furthermore, body fluids absorbed into the hydrophilic continuous skeleton of absorbent A are not easily released from the continuous skeleton (i.e., are not easily synergized), whereas body fluids absorbed into the continuous pores are easily synergized. Therefore, within the composite absorbent, the body fluids absorbed into the continuous pores are synergized and transferred to the superabsorbent polymer (SAP) with high water retention capacity, and are steadily retained within the SAP. Here, the amount of body fluid absorbed into the continuous skeleton of absorbent A and the amount of body fluid absorbed into the continuous pores are determined as follows: out of the total amount of fluid absorbed by absorbent A, the amount of body fluid that is separated from absorbent A during centrifugation (150G / 90 seconds) (amount of separated water) is the amount of body fluid absorbed into the continuous pores, and the remaining amount of body fluid (i.e. the amount of body fluid that is not separated from absorbent A during centrifugation) is the amount of body fluid absorbed into the continuous skeleton.
[0103] Furthermore, more of the body fluid absorbed by absorbent A remains in the pores than in the hydrophilic continuous skeleton. Most of the body fluid is absorbed by absorbent A by retaining the body fluid in the pores through capillary action, so the greater the porosity (the volume of the pores relative to the volume of absorbent A), which is the ratio of the volume of the voids in the pores (total pore volume), the more body fluid can be absorbed. It is preferable that this porosity is 85% or more.
[0104] For example, when the porosity of the absorbent A shown in the above-mentioned Figs. 3 to 7 is calculated, it is as follows. First, the specific surface area of absorbent A obtained by mercury porosimetry is 400 m 2 / g, and the pore volume is 15.5 mL / g. This pore volume of 15.5 mL / g means that the volume of the pores in 1 g of absorbent A is 15.5 mL. If the specific gravity of absorbent A is assumed to be 1 g / mL, the volume occupied by pores in 1 g of absorbent A, i.e., the pore volume, is 15.5 mL, and the volume of 1 g of absorbent A is 1 mL. In this case, the total volume (volume) of 1 g of absorbent A is 15.5 + 1 (mL), and the ratio of the pore volume to that is the porosity, so the porosity of absorbent A is 15.5 / (15.5 + 1) × 100 ≒ 94%.
[0105] Such an absorbent A having a hydrophilic continuous skeleton and continuous pores, i.e., a polymer absorbent, is applied in the form of, for example, particles or a sheet to a composite absorbent for absorbing body fluids such as urine and menstrual blood, such as the composite absorbent 4 of the light incontinence pad 1 described above. As described above, this polymer absorbent exhibits a unique water-absorbing behavior in which, when absorbing water, the water is first incorporated into the hydrophilic continuous skeleton and then into the continuous pores, so that it can instantly absorb a large amount of body fluid and can transfer the absorbed body fluid (mainly the body fluid absorbed into the continuous pores) to the SAP with high water-retaining capacity and steadily retain it within the SAP. Therefore, a composite absorbent using such a polymer absorbent can exhibit high absorption performance as an absorbent.
[0106] However, the water absorption amount of the polymer absorbent can be measured according to the <Method for measuring water absorption amount of polymer absorbent> below.
[0107] <Method for measuring water absorption of polymer absorbents> (1) 1 g of the measurement sample (polymer absorbent) is cut into a 10 cm square mesh bag (NBC Meshtec Co., Ltd., N-NO255HD 115 (standard width: 115 cm, 255 mesh / 2.54 cm, opening: 57 μm, wire diameter: 43 μm, thickness: 75 μm)) and enclosed. The mass (g) of the mesh bag is measured in advance. This measurement method is performed under conditions of a temperature of 25°C and a humidity of 60%. Furthermore, when the measurement sample (polymer absorbent) is to be recovered from a sanitary product and used, it can be obtained according to the <Recovery method of the measurement sample (polymer absorbent)> described below. (2) The mesh bag containing the sample is immersed in saline (0.9% sodium chloride solution) for one hour. (3) Hang the mesh bag for 5 minutes and drain, then measure its mass (g). (4) Calculate the amount of water absorption (g) of the sample by subtracting the total mass of the sample (= 1 g) and the mesh bag from the mass of the mesh bag after draining measured in (3) above, and then divide this amount of water absorption by the mass of the sample (= 1 g) to obtain the amount of water absorption per unit mass of the sample (polymer absorbent) (g / g).
[0108] When the measurement sample (polymer absorbent) is recovered from a sanitary product, it can be obtained according to the following <Method for recovering the measurement sample (polymer absorbent)>.
[0109] <How to collect the measurement sample (polymer absorbent)> (1) Peel off the top sheet or other covering from the sanitary product to expose the absorbent core. (2) Drop the object to be measured (polymer absorbent) from the exposed absorbent, and remove anything other than the (particulate) object to be measured (e.g., pulp, synthetic resin fibers, etc.) using tweezers or the like. (3) A microscope or a simple magnifying glass is used as a magnifying observation means, and the measurement object is collected using tweezers or the like while observing at a magnification at which the difference from SAP can be recognized or at which the pores of the porous body can be visually recognized. The magnification of the simple magnifying glass is not particularly limited as long as the pores of the porous body can be visually recognized, and may be, for example, 25 to 50 times. (4) The objects to be measured thus collected are used as samples for measurement in various measurement methods.
[0110] Hereinafter, the method for producing such a polymer absorbent will be described in detail using the above-mentioned absorbent A as an example.
[0111] [Method of manufacturing polymer absorbent] The above-mentioned absorbent A can be obtained through a cross-linking polymerization step and a hydrolysis step, as shown in Fig. 2. Each of these steps will be described below.
[0112] (Crosslinking polymerization process) First, an oil-soluble monomer for crosslinking polymerization, a crosslinkable monomer, a surfactant, water, and optionally a polymerization initiator are mixed to obtain a water-in-oil emulsion, which is an emulsion in which the oil phase is the continuous phase and water droplets are dispersed within it.
[0113] In the above-mentioned absorbent A, as shown in the upper diagram of Figure 2, butyl methacrylate, which is a (meth)acrylic acid ester, is used as the oil-soluble monomer, divinylbenzene is used as the cross-linking monomer, sorbitan monooleate is used as the surfactant, and isobutyronitrile is used as the polymerization initiator to cause cross-linking polymerization to obtain monolith A.
[0114] Specifically, for absorbent A, as shown in the upper diagram of Figure 2, first, 9.2 g of t-butyl methacrylate as an oil-soluble monomer, 0.28 g of divinylbenzene as a cross-linking monomer, 1.0 g of sorbitan monooleate (hereinafter abbreviated as "SMO") as a surfactant, and 0.4 g of 2,2'-azobis(isobutyronitrile) as a polymerization initiator are mixed and dissolved uniformly. Next, the mixture of t-butyl methacrylate / divinylbenzene / SMO / 2,2'-azobis(isobutyronitrile) is added to 180 g of pure water and stirred under reduced pressure using a planetary stirring device, a vacuum stirring and degassing mixer (manufactured by EME), to obtain a water-in-oil emulsion.
[0115] Furthermore, this emulsion is quickly transferred to a reaction vessel, sealed, and polymerized at 60°C for 24 hours under stationary conditions. After the polymerization is completed, the contents are removed, extracted with methanol, and then dried under reduced pressure to obtain Monolith A, which has a continuous macropore structure. The internal structure of Monolith A was observed by SEM, and it was found that Monolith A had a continuous cell structure and the thickness of the continuous skeleton was 5.4 μm. The average diameter of the continuous pores measured by mercury intrusion porosimetry was 36.2 μm, and the total pore volume was 15.5 mL / g.
[0116] The content of divinylbenzene in the total monomers is preferably 0.3 to 10 mol%, more preferably 0.3 to 5 mol%. The ratio of divinylbenzene to the total of butyl methacrylate and divinylbenzene is preferably 0.1 to 10 mol%, more preferably 0.3 to 8 mol%. In the above-mentioned absorbent A, the ratio of butyl methacrylate to the total of butyl methacrylate and divinylbenzene is 97.0 mol%, and the ratio of divinylbenzene is 3.0 mol%.
[0117] The amount of surfactant added can be set depending on the type of oil-soluble monomer and the desired size of emulsion particles (macropores), and is preferably in the range of about 2 to 70% of the total amount of the oil-soluble monomer and surfactant.
[0118] In order to control the shape and size of the bubbles in Monolith A, alcohols such as methanol and stearyl alcohol; carboxylic acids such as stearic acid; hydrocarbons such as octane, dodecane, and toluene; cyclic ethers such as tetrahydrofuran and dioxane, etc. may be allowed to coexist in the polymerization system.
[0119] In addition, the mixing method for forming the water-in-oil emulsion is not particularly limited, and any mixing method can be used, such as a method of mixing all the components at once, or a method of separately and uniformly dissolving oil-soluble components such as the oil-soluble monomer, surfactant, and oil-soluble polymerization initiator, and water-soluble components such as water and the water-soluble polymerization initiator, and then mixing the respective components.
[0120] Furthermore, the mixing device for forming the emulsion is not particularly limited, and any device such as a normal mixer, homogenizer, or high-pressure homogenizer can be used depending on the desired emulsion particle size. Furthermore, a so-called planetary mixing device can also be used in which the material to be treated is placed in a mixing container and rotated while revolving around the revolution axis while tilting the mixing container, thereby stirring and mixing the material to be treated.
[0121] In addition, there are no particular limitations on the mixing conditions, and the stirring rotation speed, stirring time, etc. can be set as desired according to the desired emulsion particle size. Note that, with the above planetary stirring device, water droplets in the W / O emulsion can be uniformly generated, and the average diameter can be set as desired within a wide range.
[0122] The polymerization conditions for the water-in-oil emulsion can be various, depending on the type of monomer and initiator, etc. For example, when azobisisobutyronitrile, benzoyl peroxide, potassium persulfate, etc. are used as the polymerization initiator, the polymerization can be carried out by heating in a sealed container under an inert atmosphere at a temperature of 30 to 100°C for 1 to 48 hours, and when hydrogen peroxide-ferrous chloride, sodium persulfate-acidic sodium sulfite, etc. are used as the polymerization initiator, the polymerization can be carried out in a sealed container under an inert atmosphere at a temperature of 0 to 30°C for 1 to 48 hours.
[0123] After the polymerization is completed, the contents are taken out and subjected to Soxhlet extraction with a solvent such as isopropanol to remove unreacted monomers and residual surfactants, thereby obtaining monolith A shown in the center diagram of Figure 2.
[0124] (Hydrolysis process) Next, the step of hydrolyzing the monolith A (crosslinked polymer) to obtain the absorbent A (hydrolysis step) will be described.
[0125] First, monolith A is immersed in dichloroethane containing zinc bromide and stirred at 40° C. for 24 hours, then contacted with methanol, 4% hydrochloric acid, 4% aqueous sodium hydroxide solution, and water in that order to carry out hydrolysis, and then dried to obtain a block-shaped absorbent A. Furthermore, this block-shaped absorbent A is crushed to a predetermined size to obtain a particulate absorbent A. Note that the form of this absorbent A is not limited to particulate, and for example, it may be formed into a sheet during or after drying.
[0126] In addition, the method of hydrolysis of monolith A is not particularly limited, and various methods can be adopted. For example, aromatic solvents such as toluene and xylene, halogen-based solvents such as chloroform and dichloroethane, ether-based solvents such as tetrahydrofuran and isopropyl ether, amide-based solvents such as dimethylformamide and dimethylacetamide, alcohol-based solvents such as methanol and ethanol, carboxylic acid-based solvents such as acetic acid and propionic acid, or water as a solvent are contacted with a strong base such as sodium hydroxide, or a hydrohalic acid such as hydrochloric acid, a Bronsted acid such as sulfuric acid, nitric acid, trifluoroacetic acid, methanesulfonic acid, and p-toluenesulfonic acid, or a Lewis acid such as zinc bromide, aluminum chloride, aluminum bromide, titanium (IV) chloride, cerium chloride / sodium iodide, and magnesium iodide.
[0127] Furthermore, among the polymerization raw materials of the organic polymer that forms the hydrophilic continuous skeleton of the absorbent A, the (meth)acrylic acid ester is not particularly limited, but is preferably a C1 to C10 (i.e., carbon number 1 to 10) alkyl ester of (meth)acrylic acid, and more preferably a C4 (i.e., carbon number 4) alkyl ester of (meth)acrylic acid. Examples of C4 alkyl esters of (meth)acrylic acid include t-butyl (meth)acrylic acid ester, n-butyl (meth)acrylic acid ester, and iso-butyl (meth)acrylic acid ester.
[0128] The monomers used in the crosslinking polymerization may be only (meth)acrylic acid esters and divinylbenzene, or may contain, in addition to (meth)acrylic acid esters and divinylbenzene, other monomers other than (meth)acrylic acid esters and divinylbenzene. In the latter case, the other monomers are not particularly limited, but examples thereof include styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, glycidyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isobutene, butadiene, isoprene, chloroprene, vinyl chloride, vinyl bromide, vinylidene chloride, tetrafluoroethylene, (meth)acrylonitrile, vinyl acetate, ethylene glycol di(meth)acrylate, and trimethylolpropane tri(meth)acrylate. The proportion of monomers other than (meth)acrylic acid ester and divinylbenzene in all monomers used in the crosslinking polymerization is preferably from 0 to 80 mol %, more preferably from 0 to 50 mol %.
[0129] The surfactant is not limited to the above-mentioned sorbitan monooleate, and may be any surfactant capable of forming a water-in-oil type (W / O) emulsion when the monomer for crosslinking polymerization is mixed with water. Examples of such surfactants include nonionic surfactants such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan trioleate, polyoxyethylene nonylphenyl ether, polyoxyethylene stearyl ether, and polyoxyethylene sorbitan monooleate, anionic surfactants such as potassium oleate, sodium dodecylbenzenesulfonate, and dioctyl sodium sulfosuccinate, cationic surfactants such as distearyl dimethyl ammonium chloride, and amphoteric surfactants such as lauryl dimethyl betaine. These surfactants may be used alone or in combination of two or more.
[0130] In addition, the polymerization initiator is preferably a compound that generates radicals by heat and light irradiation. Furthermore, the polymerization initiator may be water-soluble or oil-soluble, and examples thereof include azobis(4-methoxy-2,4-dimethylvaleronitrile), azobisisobutyronitrile, azobisdimethylvaleronitrile, azobiscyclohexanenitrile, azobiscyclohexanecarbonitrile, azobis(2-methylpropionamidine)dihydrochloride, benzoyl peroxide, potassium persulfate, ammonium persulfate, hydrogen peroxide-ferrous chloride, sodium persulfate-acidic sodium sulfite, and tetramethylthiuram disulfide. However, in some cases, there are systems in which polymerization proceeds only by heating or light irradiation without the addition of a polymerization initiator, and in such systems, the addition of a polymerization initiator is not necessary. EXAMPLES
[0131] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0132] (A) Sample (a) Pore distribution The polymer absorbents of the present invention manufactured by the above manufacturing method were used as samples of Examples 1 to 5, and Infinity particles were used as samples of Comparative Examples 1 and 2. However, for the samples of Examples 1 to 5, the surfactant / monomer ratio (wt%) and the stirring time (min) were changed when forming the water-in-oil type emulsion in the manufacturing method. Infinity particles are absorbents manufactured by P&G, and although they have a structure (foam structure) similar to that of polymer absorbents, they do not have the function of absorbing water and expanding, unlike polymer absorbents. (b) Relationship between bulk density and water absorption rate Regarding the samples of the above examples, samples with various bulk densities were prepared by changing the conditions of ethanol immersion and drying. Specifically, the dried polymer absorbent was thoroughly immersed in a 40% ethanol aqueous solution, and then the supernatant liquid was removed and ethanol was added repeatedly to adjust the ethanol aqueous solution to a predetermined concentration. After thorough immersion, the wet polymer absorbent was filtered and dried overnight at 50°C under reduced pressure to obtain polymer absorbents with different bulk densities.
[0133] (B) Evaluation (a) Pore distribution Using mercury intrusion porosimetry, the cumulative (integrated) pore volume distribution (relationship between pore radius and cumulative pore volume) and log differential pore volume distribution (relationship between pore radius and log differential pore volume) were determined for each sample, and the total pore volume (mL / g), average pore radius (μm), maximum pore radius (μm), pore volume (proportion) of pores with a specified pore radius or more (or less), and pore volume variation coefficient were calculated. (b) Relationship between bulk density and water absorption rate In the measurement of water absorption rate (DW), the relationship between the bulk density and water absorption rate (DW) of each sample was investigated.
[0134] (C) Evaluation Results (a) Pore distribution The measurement results are shown in Figures 8 and 9, and a summary of the results is shown in Table 1. Note that Figure 8 shows the obtained cumulative (integrated) pore volume distribution, i.e., the relationship between the pore radius (horizontal axis) and the cumulative pore volume (vertical axis), and Figure 9 shows the obtained log differential pore volume distribution, i.e., the relationship between the pore radius (horizontal axis) and the log differential pore volume (vertical axis). Note that in Figures 8 and 9, Example 1 is a dashed line (thick line), Example 2 is a dashed line (thin line), Example 3 is a dashed line (thin line), Example 4 is a dotted line, Example 5 is a solid line (thin line), Comparative Example 1 is a solid line (thick line), and Comparative Example 2 is a dashed line (thick line).
[0135] [Table 1] *Pore radius 1μm or more
[0136] For the samples of Examples 1 to 5, the following was confirmed. The ratio of the pore volume of pores with a pore radius of 1 μm or more was 90% or more of the pore volume of all pores. The ratio of the pore volume of pores with a pore radius of 0.005 μm or less was less than 10% of the pore volume of all pores. The pore radius at the maximum pore volume was 500 μm or less. The coefficient of variation of the pore distribution in pores with a pore radius of 1 μm or more was sometimes 1.4 or less (Example 3). The coefficient of variation of the pore distribution in pores with a pore radius of 1 μm or more was sometimes more than 1.4 (Examples 4 and 5). In the curve showing the pore distribution, the part on the side with a larger pore radius was broader than the part on the side with a smaller pore radius with respect to the pore radius corresponding to the maximum value of the pore volume in the curve showing the pore distribution (Example 5). In the curve showing the pore distribution, the part on the side with a smaller pore radius was broader than the part on the side with a larger pore radius with respect to the pore radius corresponding to the maximum value of the pore volume in the curve showing the pore distribution (Example 4). There were at least two maximum values of the pore volume in the curve showing the pore distribution (Examples 1 and 2). In the curve showing the pore distribution, the maximum value of the relatively small pore radius was larger than the maximum value of the relatively large pore radius in some cases (Example 2). In the curve showing the pore distribution, the maximum value of the relatively small pore radius was smaller than the maximum value of the relatively large pore radius in some cases (Example 1). The total pore volume was 0.9 mL / g or more. On the other hand, in Comparative Examples 1 and 2, the proportion of the pore volume of pores with a pore radius of 1 μm or more was less than 90% of the pore volume of all pores.
[0137] (b) Relationship between bulk density and water absorption rate The measurement results are shown in Figure 10. Figure 10 is a graph showing the relationship between the obtained bulk density (horizontal axis) and the water absorption rate (vertical axis). As shown in the figure, the bulk density was 0.07 to 0.6 g / cm 3 It was confirmed that the water absorption rate (DW) performance can be increased to 6mL / 30sec. or more by setting the bulk density to 0.1-0.4g / cm 3 It was confirmed that the water absorption rate (DW) performance can be increased to 10 mL / 30 sec. or more by setting the bulk density to 0.15 to 0.35 g / cm. 3It was confirmed that by doing so, the water absorption rate (DW) performance can be increased to 12 mL / 30 sec. or more.
[0138] In addition to the light incontinence pads of the above-mentioned embodiments, the composite absorbent of the present invention can be applied to various sanitary products, such as pants-type disposable diapers, tape-type disposable diapers, sanitary napkins, absorbent liners, absorbent pads (e.g., bedsore pads and postpartum pads), absorbent sheets, breast milk pads, disposable diapers for pets, absorbent pads for pets, pet waste disposal sheets, wet sheets, wet tissues, cosmetic wipes, masks, etc. Therefore, the body fluids to be absorbed by the composite absorbent are liquids discharged from the wearer of the sanitary product, such as urine, sweat, feces, menstrual blood, vaginal discharge, breast milk, blood, exudates, etc.
[0139] Furthermore, the present invention is not limited to the above-described embodiments, and appropriate combinations, substitutions, modifications, etc. are possible without departing from the scope and spirit of the present invention. [Explanation of symbols]
[0140] 1. Light incontinence pads 2 Surface sheet 3 Back sheet 4. Composite absorber
Claims
1. 1. A composite absorbent body for sanitary products for absorbing body fluids, comprising: The present invention relates to a polymeric absorbent material having a hydrophilic continuous skeleton and continuous pores, In the polymer absorbent, the ratio of the pore volume of pores having a pore radius of 1 μm or more to the pore volume of all pores is 90% or more, In the polymer absorbent, the coefficient of variation of the pore distribution is more than 1.4 in pores having a pore radius of 1 μm or more. Composite absorber.
2. In the polymer absorbent, the ratio of the pore volume of pores having a pore radius of 0.005 μm or less is less than 10% of the pore volume of all pores.
2. The composite absorbent body of claim 1.
3. 3. The composite absorbent according to claim 1 or 2, wherein the polymer absorbent has a pore radius at the maximum pore volume of 500 μm or less.
4. The composite absorbent according to any one of claims 1 to 3, characterized in that in the polymer absorbent, a portion on the side of a larger pore radius is broader than a portion on the side of a smaller pore radius with respect to a pore radius corresponding to a maximum value of the pore volume in a curve showing the pore distribution.
5. The composite absorbent according to any one of claims 1 to 3, characterized in that in the polymer absorbent, a portion on the side where the pore radius is smaller is broader than a portion on the side where the pore radius is larger, with respect to a pore radius corresponding to a maximum value of the pore volume in a curve showing the pore distribution.
6. A composite absorbent for use in sanitary products for absorbing body fluids, comprising: The present invention relates to a polymeric absorbent material having a hydrophilic continuous skeleton and continuous pores, In the polymer absorbent, the ratio of the pore volume of pores having a pore radius of 1 μm or more to the pore volume of all pores is 90% or more, A composite absorbent body, characterized in that in the polymer absorbent, there are at least two maximum values of pore volume in a curve showing the pore distribution.
7. The composite absorbent according to claim 6, characterized in that in the polymer absorbent, the two maximum values of pore volume in the curve showing the pore distribution are such that the maximum value of the relatively small pore radius is larger than the maximum value of the relatively large pore radius.
8. The composite absorbent of claim 6, characterized in that in the polymer absorbent, the two maximum values of pore volume in the curve showing the pore distribution are such that the maximum value of the relatively small pore radius is smaller than the maximum value of the relatively large pore radius.
9. The composite absorbent according to any one of claims 1 to 8, wherein the polymer absorbent has a total pore volume of 0.9 mL / g or more.
10. The polymer absorbent has a bulk density of 0.07 to 0.6 g / cm 3 The composite absorbent body according to any one of claims 1 to 9,
11. The composite absorbent according to any one of claims 1 to 10, wherein the polymer absorbent is a monolithic absorbent.
12. The composite absorbent according to any one of claims 1 to 11, characterized in that the polymer absorbent is a hydrolysate of a crosslinked polymer of a (meth)acrylic acid ester and a compound containing two or more vinyl groups in one molecule, and contains at least one or more -COONa groups.
13. A sanitary product comprising the composite absorbent body according to any one of claims 1 to 12.
Citation Information
Patent Citations
Absorptive article
JP1994070953A
Thin until wet, absorbent foam material for aqueous body fluids and method of making same
JP1996504474A
Absorbent material structures, methods of manufacture and uses thereof, and disposable absorbent articles containing such material structures
JP2002505702A
Surface treatment method for water-absorbent resins
JP2011500874A
Absorbent foam materials for aqueous body fluids and absorbent articles containing such materials
JP3231320B2